S85. MANAGEMENT OF PHYSICAL HEALTH FOR PEOPLE WITH SCHIZOPHRENIA IN PRIMARY CARE: A SYSTEMATIC REVIEW. (18th May 2020) - Wiener, Joshua; Rodrigues, Myanca; Anderson, Kelly
Abstract: Background: We sought to determine how the physical health of people with schizophrenia is managed by family physicians in a primary care setting relative to those without schizophrenia. Methods: A comprehensive literature search was conducted in three electronic databases for articles published in English up to January 2019. Studies were included if: (1) study design was observational; (2) population was patients receiving primary care from family physicians; (3) exposure was schizophrenia; (4) comparison was no schizophrenia; and (5) outcome was management of physical health condition. Study details, subject characteristics, methods, and results were extracted from each study and summarized in a qualitative manner. Risk of bias (RoB) for each study was assessed using the CLARITY tool. Results: A total of 12 articles met inclusion criteria, including 9 retrospective cohort studies with low RoB and 3 case control studies with moderate RoB. Among patients with diabetes (5 studies), those with schizophrenia received lower rates of guideline-recommended monitoring. Among patients with cardiovascular disease (2 studies), those with schizophrenia received lower rates of guideline-recommended prescriptions (e.g., statins). Among patients at risk for cardiovascular disease (3 studies), those with schizophrenia received lower rates of guideline-recommended screening (e.g., serum cholesterol levels). Among patients at risk for cancer (2 studies), those with schizophrenia received lower rates of guideline-recommended screening (e.g., Papanicolaou test). Discussion: Physical health management is an ongoing concern for individuals living with schizophrenia. These individuals often receive poorer care of their physical health by family physicians when compared to individuals without schizophrenia.